Gender inequality during the COVID-19 pandemic: Income, expenditure, savings, and job loss - Dang, Hai-Anh H.; Viet Nguyen, Cuong (World development, 2021)
•This study examines COVID-19 impacts on gender gaps in economic outcomes.•Women to be 24 percent more likely to permanently lose their job than men.•Women expect their labor income to fall by 50 percent more than men do.•Women tend to reduce their current consumption and increase savings.•Country heterogeneity is likely due to varying infection rates and shares of women in the labor force. The COVID-19 outbreak has brought unprecedented disruptions to the global economies and has led to income loss and high unemployment rates. But scant, if any, evidence exists on gender gaps in economic outcomes such as income, expenditure, savings, and job loss in a multi-country setting. We investigate the impacts of COVID-19 on gender inequality in these outcomes using data from a six-country survey that covers countries in different geographical locations and at various income levels. Our findings suggest that women are 24 percent more likely to permanently lose their job than men because of the outbreak. Women also expect their labor income to fall by 50 percent more than men do. Perhaps because of these concerns, women tend to reduce their current consumption and increase savings. Factors such as the different participation rates in work industries for men and women may take an important part in explaining these gender gaps. Our estimates also point to country heterogeneity in these gender differences that is likely due to varying infection rates and shares of women in the labor force.